Awareness Of Allergic Conjunctivitis and Its Impact on Parents of School-Going Children Visiting Eye Clinic in A Speciality Hospital in Chengalpattu District: A Cross- Sectional Study - M, Rishwanth; C, Shankar; G, Premnath; Bravian, Shinisha Paul; R, Ishwarya (Journal of Neonatal Surgery, 2025)
Introduction: Allergic conjunctivitis, a common form, affects 6% to 30% of people globally and up to 40% in some studies. In India, rates have increased due to environmental factors like pollen, dust mites, pollution, and climate conditions. Symptoms include itching, swelling, tearing, and sometimes pain or light sensitivity. Many parents lack awareness of ocular allergies, which affects children's treatment and daily functioning. Improving education for parents can help identify symptoms early and support children better. This study highlights the need for better community education to address gaps in knowledge and reduce the impact of ocular allergies on families. Methodology: This cross-sectional study involved 440 parents of school-going children attending pediatric and ophthalmology OPD in a tertiary care hospital near Chennai. Data was collected using a tested questionnaire on awareness of a specific condition. Analysis used Welch’s ANOVA, T tests, and Chi-Square tests after checking data assumptions. Ethical approval and confidentiality were maintained throughout. Results: The participants’ mean knowledge score showed significant differences based on their level of education (p-value < .001), primary source of knowledge (p-value < .001), past history of allergic conjunctivitis in their children (p-value < .001). A significant negative association was noted between the factors, awareness of symptomatic management of allergic conjunctivitis and the burden of the disease on the child and parent. Chemicals from vehicle fumes are of increasing concern but not as much as other known allergens like pollen, hay, mold, pet dander etc., (p-value < .001). Conclusion: Allergic conjunctivitis affects more than comfort; it can disrupt school, home life, and work. Understanding how to manage triggers and use safe home remedies reduces this impact. Parents who learn about allergic conjunctivitis can help their children attend school consistently and maintain regular family routines. Accurate information from healthcare providers is more helpful than relying on internet searches or social media. Trusted advice offers practical ways to handle symptoms and speed recovery. Common allergens such as pet dander, mold, and vehicle emissions are increasing in cities. Recognizing these triggers and reducing exposure lowers stress for both parents and children. Access to reliable information is essential for effective management